Avaliação do pH na amostra isolada e na urina de 24h de pacientes litiásicos em uso de citrato de potássio - Silva, Isabela Bertanholi Leme da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
INTRODUCTION: Urinary lithiasis (UL) is a highly prevalent condition in clinical practice, and has been known for centuries. In most patients, recurrent calculi composition is similar to the original ones, suggesting that it may be a multifactorial process, also influenced by urine characteristics. Thus, urinary pH variation may have an important role in calculus composition. Classically, 24-h urine collection (U24-h) is considered one of the most useful tools in investigation and treatment of urinary lithiasis etiology. However, this test is cumbersome to perform. Recent research suggests that a fasting urine pH may be as representative as U24-h. Therefore, further studies are necessary to determine the ideal methodology for evaluating and monitoring the urinary pH in patients with nephrolithiasis. SUBJECTS AND METHODS: A total of 114 patients with nephrolithiasis that are in use of citrate potassium were prospectively evaluated. All patients collected 24-h urine (U24h); and an aditional fasting sample was obtained (Uf) when delivering the first one at the lab. Two different methods (pH test paper and digital pHmeter) were used for the urinary pH determination. RESULTS: Among the 114 individuals evaluated, 44 (39%) were male and 70 (61%) female; mean age was 51.11 ± 12.93 years old and average body mass index (BMI) was 28.71 ± 4.56 kg / m2. Mean U24-h pH for test paper was 6.07 ± 0.74 and 6.02 ± 0.82 for Uf. Likewise, considering the digital pHmeter methodology, mean pH was 5.8 ± 0.78 and 5.75 ± 0.83, for U24-h and Uf, respectively. There was a good statistical correlation between urinary pH values obtained from pH test paper and pHmeter, for both types of urine sample (U24-h and Uf). CONCLUSION: The pH measurement in fasting urine sample was as effective as the standard method (U24-h) in the evaluation of patients with nephrolithiasis using potassium citrate

INTRODUÇÃO: A Litíase do Trato Urinário (LTU) é uma afecção altamente prevalente na prática clínica diária, sendo conhecida há vários séculos. Sabe-se que, na maioria dos pacientes, os cálculos recorrentes apresentam composição similar aos previamente formados, sugerindo que este processo seja multifatorial e influenciado também pelas características da urina. Neste sentido, a variação do pH urinário exerceria papel fundamental na composição do cálculo renal. Classicamente, a urina 24h tem se constituído como uma das mais importantes ferramentas auxiliares na investigação e no tratamento dos fatores envolvidos na etiologia da LTU. Entretanto, a coleta desse tipo de exame apresenta grandes dificuldades práticas. Pesquisas recentes sugerem que a determinação do pH urinário obtido em amostra isolada de urina poderia ser tão representativa quanto a dosagem realizada na urina de 24 horas. Diante do exposto, novos estudos são necessários para auxiliar na determinação da metodologia ideal de avaliação e monitoramento do pH urinário em pacientes portadores de litíase renal. PACIENTES E MÉTODO: Foram avaliados prospectivamente 114 pacientes, portadores de litíase renal, acompanhados no ambulatório de metabolismo em nefrolitíase do Hospital de Clinicas da Faculdade de Medicina de Botucatu. Após análise das principais características clínicas, todos os pacientes realizaram coleta de urina de 24 horas (U24h) e, uma segunda amostra foi obtida em jejum (Ujj), no dia da entrega do exame. Duas metodologias distintas (tira reagente e a leitura com pHmetro digital) foram empregadas para a determinação dos valores de pH urinário. RESULTADOS: Dos 114 indivíduos avaliados, 44 (39%) eram homens e 70 (61%) mulheres, com média de idade de 51,11 ± 12,93 anos. O índice de massa corporal médio (IMC) foi de 28,71 ± 4,56 Kg/m2. Na U24h, a análise do pH por tira reagente apresentou pH médio de 6,07 ± 0,74; valor ...
Action of the pH in isolated sample and 24h urine of lithiasis patients in use potassium citrate
Keywords: Urina - Analise; Aparelho urinário - Cálculos; Infecções urinarias; Rins - Calculos